Alienation and beauty in medical photography. (3rd July 2018) - Barnett, Lauren
Abstract: Though photography was initially touted to overtake medical illustration as a more objective medium, today photographs are underused in medical texts. The concern with aesthetics and the relationship between the body and the patient combined to shape the future of medical photography, and in some ways medicine itself. Closely examining two cases – Duchenne's 'Mécanisme de la Physionomie Humaine' (1856), and Grant's 'An Atlas of Anatomy' (1962) – I consider the role of alienation and beauty in medical photography and the evocative questions each raised in medical history. This is adapted from a talk given at RCPE.